1, 213 Cases of Treatment of Facial Acne Using Indocyanine Green and Intense Pulsed Light in Asian Skin. (18th October 2015) - Park, Kui Young; Kim, Ji Young; Hyun, Moo Yeol; Oh, Won Jong; Jeong, Se Yeong; Han, Tae Young; Ahn, Ji Young; Kim, Beom Joon; Kim, Myeung Nam
Abstract : Background . Photodynamic therapy (PDT) has been used for acne, with various combinations of photosensitizers and light sources. Objective . We evaluated the effectiveness and safety of indocyanine green (ICG) and intense pulsed light (IPL) in the treatment of acne. Materials and Methods . A total of 1, 213 patients with facial acne were retrospectively reviewed. Patients received three or five treatments of ICG and IPL at two-week intervals. Clinical response to treatment was assessed by comparing pre- and posttreatment clinical photographs and patient satisfaction scores. Results . Marked to excellent improvement was noted in 483 of 1, 213 (39.8%) patients, while minimal to moderate improvement was achieved in the remaining 730 (60.2%) patients. Patient satisfaction scores revealed that 197 (16.3%) of 1, 213 patients were highly satisfied, 887 (73.1%) were somewhat satisfied, and 129 (10.6%) were unsatisfied. There were no significant side effects. Conclusion . These results suggest that PDT with ICG and IPL can be effectively and safely used in the treatment of acne.